Desafios e tensões de professores de matemática na dinamização de discussões em temas da Álgebra - Rodrigues, Cátia (2020)
Whole class discussions have come to be seen in mathematics teaching as a tool available to teachers to promote their students’ learning, insofar as they can involve them in the presentation and justification of previously selected strategies for solving mathematical tasks. In these discussions, the teacher relies on his/her didactic knowledge of mathematics to carry out a set of teaching actions to involve the students in the classroom discourse. The orchestration of these actions generates tensions in teachers, especially when they try to reconcile the discussion of important mathematical ideas with students’ participation. In this research, part of a larger study, we try to understand the tensions that three mathematics teachers face in leading whole class discussions based on algebraic tasks and how they try to overcome them. This qualitative and interpretative study is based on case studies of three teachers who are part of a collaborative group. Data were collected by interview, participant observation of teachers’ classes and collaborative work sessions and documentary analysis. Data analysis is based on a recursive process that led to the construction of formal categories, supported by the theoretical framework. The results show that teachers face diverse tensions when they try to involve the students in sharing and justifying algebraic ideas, recognizing that collaboration and planning the discussions are important mechanisms to help them cope with these tensions.